A conceptual framework integration of UTAUT and HBM on evaluating the adoption of electronic payment system in Malaysia - Jaafar, Ishaq; Tasmin, Rosmaini; Ramlan, Rohaizan; Abdul Hamid, Nor Aziati; Ngadiman, Yunos (Penerbit UTHM, 2020)
Most recently, financial technology services such as e-wallet, automated teller machines, credit and debit card and smartphones are used to conduct different forms of financial payment. Therefore, any form of technology that provides the medium to which electronic payment can be initiated or confirmed (Geva, 2012). This study focuses on the individual intention to use electronic payment systems. This is because the electronic payment system is faced with the related risk to security and privacy (Ivarsson, 2008).